JIHAD GENDER: SEBUAH PEMBACAAN HERMENEUTIKA - Farichatul Maftuchah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
Between men and women really are not too many differences. In the eyes of Allah SWT, the male and femaleundifferentiated. Teir good or bad, only determined by their taqwa. However, in everyday life, women are often regarded as second class.According to the author, that statement is an implication of superiority of men, not a theological view, but more to the sociological. Menwith avariety of interpretations all the way to prove to the public that women are second class. Obviously, this understanding needs to be reviewedto find the real truth. This paper describes some misinterpretation of the Koran. The actual interpretation based only on the superiority ofmen. Therefore, the need for reading by using hermeneutics to understand the truths contained in them.